Parenting Processes Mediate the Link Between Maternal Depressive Symptoms and Adolescent Psychopathology. - Reigstad, Kristina M.; Marceau, Kristine; Gunlicks-Stoessel, Meredith L.; VanZomeren, Adrienne A.; Westervelt, Ana; Brand, Ann E.; Zahn-Waxler, Carolyn; Hastings, Paul D.; Klimes-Dougan, Bonnie (Journal of Child & Family Studies, 2023)
There is now strong evidence documenting an association between maternal depression and psychopathology in children and adolescents, but an increased understanding of the explanatory mechanisms is needed. This longitudinal study tested a model to determine if parenting processes that may promote parentification of adolescents (coded from narratives written by mothers) mediate the link between maternal depression symptoms and adolescent psychopathology. Participants in this study were 220 mothers and their children between the ages of 11 and 17, over-recruited for adolescent psychopathology. Maternal depression symptoms and the understudied process of differentiation of generational boundaries, as well as more commonly evaluated aspects of self-efficacy and child acceptance, were evaluated at Time 1. Adolescent psychopathology was assessed at Time 1 and again two years later at Time 2. As predicted maternal depression symptoms were related to adolescent psychopathology and this link was partially mediated by parenting processes. Some differences in these results were shown for adolescent females and males. Findings highlight parental mechanisms by which risk for psychopathology may be transmitted across generations and suggest avenues for clinical interventions. Highlights: This study tested a model to determine if specific aspects of parenting that may promote parentification of adolescents mediate the link between maternal depression symptoms and adolescent psychopathology. We developed and tested a narrative coding system to evaluate parenting processes of differentiation of generational boundaries, parental self-efficacy and acceptance. Maternal depression symptoms were related to adolescent psychopathology, and this link was partially mediated by parenting processes. The longitudinal findings suggest that the mechanisms differ, for girls differentiated boundaries and for boys self-efficacy/acceptance. Findings highlight parental mechanisms by which risk may be transmitted across generations and suggest avenues for clinical interventions.